Police Role In The Process Of Penal Mediation - Agus Triatmoko; Anis Mashdurohatun (Jurnal Daulat Hukum, 2018)
Penal mediation settlement of criminal cases into the shape desired by the people involved in the dispute or disputes between community members. This is caused because the penal mediation there is no one party that defeated or won, so hopefully after the settlement with this penal mediation model disputing community members can live in peace side by side back to normal. This study raises the issue. What is the role of the police in the process penal mediation? This study belongs to the species normative legal research. Technic collecting data used is the study of literature. Descriptive analysis method. The results showed that that the implementation of the Police has the authority to conduct penal mediation by Act No. 2 of 2002 on the Indonesian National Police. One form of penal mediation by the police that the decision to terminate the criminal case after the settlement reached through negotiation involving mainly the victims and perpetrators, as well as religious leaders, community leaders and local government representatives.Keyword: Police, Penal Mediation, Criminal Case.